Annual Plan Proposals 1965-66 Goa, Daman and Diu - Planning Commission (Planning Commission, 1966)
After the change-over in December 1961, a Outlay & Planning-Board was constituted the Union Territory of Goa, Daman and Diu and proposal for the remaining three years of the Third Five Year Plan were submitted to the Planning Commission. The Territory prepared a Development Plan and allocations are being made through the Annual Plans. Many of the projects and Programme have been technically approved. In view of the fact that the Government of the Territory started without the background and facilities of planning of economic and social development as in the case of Governments of other States and Territories and view of the fact that the Territory should be .helped to. The extent possible to make up the backlog of development, a somewhat more flexible approach has been kept in considering the proposals of the Government of Goa in the Annual Plans during successive years.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Organization of Cooperation Department; Fisheries; On Development Plan Technical Education; Irrigation Projects; Mineral Development; Large & Medium Scale Industries; Public Works Department; Welfare of Backward Classes; Community Development Programme; Public Cooperation; Cultural Activities